Synthesis and Characterization of Partially Reduced Graphene Oxide and Platinum and Gold Partially Reduced Graphene Oxide. Issue 19 (2nd February 2016) - Isseroff, Rebecca; Blackburn, Lee; Chen, Arthur; Gentleman, Molly; Rafailovich, Miriam
ABSTRACT: While graphene has unique electrical and mechanical properties, it is not soluble in most common solvents. Partially reducing graphene oxide (prGO) will remove some of the functional groups while still maintaining solubility, producing an intermediate between graphene oxide and reduced graphene oxide. This research investigated the properties of prGO as well as those of prGO sheets incorporated with gold and platinum nanoparticles (Au/Pt-prGO) using FTIR, Raman, TEM and HRTEM.